Prospects and challenges of outsourcing in the context of power grid company of Bangladesh limited - Shihab, Mohammad Abdullah (BRAC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.